YaeL proteolysis of RseA is controlled by the PDZ domain of YaeL and a Gln-rich region of RseA - Kanehara, Kazue (Oxford University Press, 2003)
σ(E) is an alternative sigma factor involved in a pathway of extracytoplasmic stress responses in Escherichia coli. Under normal growth conditions, σ(E) activity is down-regulated by the membrane-bound anti-σ(E) protein, RseA. Extracytoplasmic stress signals induce degradation of RseA by two successive proteolytic events: DegS-catalyzed first cleavage at a periplasmic site followed by YaeL-mediated second proteolysis at an intramembrane region. Normally, the second reaction (site-2 proteolysis) only occurs after the first cleavage (site-1 cleavage). Here, we show that YaeL variants with the periplasmic PDZ domain deleted or mutated allows unregulated cleavage of RseA and consequent σ(E) activation. It was also found that a glutamine-rich region in the periplasmic domain of RseA was required for the avoidance of the YaeL-mediated proteolysis in the absence of site-1 cleavage. These results indicate that multiple negative elements both in the enzyme (PDZ domain) and in the substrate (glutamine-rich region) determine the strict dependence of the site-2 proteolysis on the site-1 cleavage.